Development of Insertion and Deletion Markers based on Biparental Resequencing for Fine Mapping Seed Weight in Soybean. Issue 3 (1st November 2014) - Li, Ying‐hui; Liu, Bo; Reif, Jochen C.; Liu, Yu‐lin; Li, Hui‐hui; Chang, Ru‐zhen; Qiu, Li‐j uan
Abstract : As a complement to single nucleotide polymorphisms (SNPs) and simple sequence repeats (SSRs), biallelic insertions and deletions (InDels) represent powerful molecular markers with desirable features for filling the gap in current genetic linkage maps. In this study, 28, 908 small InDel polymorphisms (1–5 base pair, bp) distributed genome‐wide were identified and annotated by comparison of a whole‐genome resequencing data set from two soybean [ Glycine max (L.) Merr.] genotypes, cultivar Zhonghunag13 (ZH) and line Zhongpin03‐5373 (ZP). The physical distribution of InDel polymorphisms in soybean genome was uneven, and matched closely with the distribution of previously annotated genes. The average density of InDel in the arm region was significantly higher than that in the pericentromeric region. The genomic regions that were fixed between the two elites were elucidated. With this information, five InDel markers within a putative quantitative trait locus (QTL) for seed weight (SW), qSW‐17‐2, were developed and used to genotype 254 recombinant inbred lines (RILs) derived from the cross of ZP × ZH. Adding these five InDel markers to previously used SNP and SSR markers facilitated the discovery of further recombination events allowing fine‐mapping the QTL to a 0.5 Mbp region. Our study clearly underlines the high value of InDel markers for map‐based cloning and marker‐assisted selection in soybean.